Alternatives to Democracy in Twentieth-Century : Collectivist Visions of Alternative Modernity - Ramet, Sabrina P., 1949- (CEU Press, 2019)
"An original work of historical synthesis by an esteemed international scholar, this book offers the first comparative analysis of the four different types of collectivism (communism, Fascism; Nazism; anarchism) in twentieth-century Europe which aspired to create an 'alternative modernity'. The author presents not only the authoritarian alternatives to democracy of the past century, but also the experiment with anarchism undertaken in Spain in the late 1930s. The concept of the analysis is to show how these political systems are driven by rival visions of alternative modernity and how the prioritization of values plays out in politics. Each political concept discussed in the book found support among broad sectors of its respective population at one time or another, and were championed by professionals in the countries in which they took hold. The political vision which guided the construction (or in the anarchist case, attempted construction) of an alternative to democracy, oriented to an alternative future, is discussed in a balanced and erudite manner in each case. Debates within the participants in these projects are also focused. The book ends with a defense of liberal democracy, exploring departures from it in contemporary Hungary and Poland, but also the US"--